rozwiaz nierownosc -3(x-1)^2<-27

Odpowiedź :

- 3(x - 1)² < - 27

- 3(x² - 2x + 1) < - 27

- 3x² + 6x - 3 < -27

- 3x² + 6x + 24 < 0 /:3

- x² + 2x + 8 < 0

Δ = 4 + 32 = 36

√Δ = 6

[tex]x_{1} =\frac{-2+6}{-2} =-2\\x_{2} =\frac{-2-6}{-2} =4[/tex]

x ∈ (-∞, -2) ∪ (4, ∞)

Zobacz obrazek Kamikamika

Odpowiedź:

Szczegółowe wyjaśnienie:

- 3(x - 1)² < - 27     /:(-3)   ⇒

(x - 1)² > -27/-3   ⇒    (x - 1)² > 9    

(x - 1) < - 3  ∨  (x - 1) > 3  ⇒ (x  < - 3 + 1)  ∨  (x > 3 + 1)  

(x  < - 2)  ∨  (x > 4)  ⇒  x ∈ {(- ∞, -2) ∪ (4, ∞)}

Viz Inne Pytanie